2022
DOI: 10.1126/science.add5064
|View full text |Cite
|
Sign up to set email alerts
|

Craspase is a CRISPR RNA-guided, RNA-activated protease

Abstract: The Type III-E RNA-targeting effector complex (gRAMP/Cas7-11) is associated with a caspase-like protein (TPR-CHAT/Csx29) to form Craspase (CRISPR-guided caspase). Here we use cryo-electron microscopy snapshots of Craspase to explain its target RNA cleavage and protease activation mechanisms. Target-guide pairing extending into the 5′ region of the guide RNA displaces a gating loop in gRAMP, which triggers an extensive conformational relay that allosterically aligns the protease catalytic dyad and opens an amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 39 publications
6
83
0
Order By: Relevance
“…Furthermore, we provide a mechanism for self versus non-self RNA target discrimination governed by conformational change-induced activation of the TPR-CHAT protease in type III-E CRISPR-Cas antiviral immunity. While our manuscript was under review, several studies 42 47 reported the structural and functional insights of type III-E Craspase complexes; these independent studies are overall in agreement with our results.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, we provide a mechanism for self versus non-self RNA target discrimination governed by conformational change-induced activation of the TPR-CHAT protease in type III-E CRISPR-Cas antiviral immunity. While our manuscript was under review, several studies 42 47 reported the structural and functional insights of type III-E Craspase complexes; these independent studies are overall in agreement with our results.…”
Section: Discussionsupporting
confidence: 88%
“…The major difference between these two structure is that the Cas11 domain rotates about 30 °, and the Insertion domain is not observed in our structure due to flexibility (Figure S6). Recently, Nishimasu’s group has resolved the cryo-EM structures of the DiCas7-11-crRNA-Csx29 complex with and without target RNA 11 . In the structure of DiCas7-11-crRNA-Csx29-tgRNA, the CTD of Csx29 (residues 75-751) is not observed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Nishimasu's group has resolved the cryo-EM structures of the DiCas7-11-crRNA-Csx29 complex with and without target RNA 11 . In the structure of DiCas7-11-crRNA-Csx29-tgRNA, the CTD of Csx29 (residues 75-751) is not observed.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, it allosterically activates a different effector, the TPR-CHAT protease, in a 3’ PFS-dependent manner. Though 13 of the 15 5’-tag nucleotides are buried by the protein, the last two, C(–1) and A(–2), are partially solvent-accessible and can potentially participate in PFS-mediated activation of the TRP-CHAT activity ( Hu et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%